The Adaptation and Validation of the Turkish Version of the Personal Report of Public Speaking Anxiety (PRPSA) - Yirci, Ramazan; Kartal, Secil Eda; Ozdemir, Tuncay Yavuz; Karakose, Turgut; Kocabas, Ibrahim (Univ Autonoma Baja California, Inst Investigacion & Desarrollo Educativo, 2018)
The purpose of this study is to adapt the Personal Report of Public Speaking Anxiety (PRPSA) scale into Turkish and study its validity and reliability. The original form of the scale has a single-factor structure and consists of 34 items. The study sample was composed of a total of 322 candidate teachers studying in the School of Education. Three items with fit values below 0.30 from the corrected item-total correlation were excluded from the scale and the analyses were conducted on the remaining 31 items. The construct validity of the scale was confirmed as a single factor through the Mplus software. Cronbach's alpha for the scale was 0.94, indicating that the scale also has a high level of reliability in the Turkish form. No significant differences were detected between male and female participants' speaking anxiety scores.
Keywords: Public speaking; anxiety; rating scales